Mapping the global, regional, and national burden of diarrheal diseases attributable to unsafe water - Chen, Ling; Jiao, Jinghua; Liu, Shunming; Liu, Lei; Liu, Pengliang (Frontiers in Public Health, 2023)
Background Diarrhoeal diseases are major contributors to deaths. Data on global and country-specific levels and trends of diarrhoeal diseases resulting from unsafe water are essential for policymakers to allocate resources. Aims In order to describe the global, regional, and national spatio-temporal burden of diarrhoeal diseases resulting from unsafe water exposure. Methods According to the Global Burden of Disease (GBD) 2019 dataset, deaths, disability-adjusted life years (DALYs) of diarrhoeal diseases and their age-standardized rates (ASR) were analyzed by age and sex in 204 countries and territories. Moreover, the average annual percentage change (AAPC) was estimated by a log-linear regression model to reflect the time trend. The association between ASR of diarrhoeal diseases due to unsafe water and socio-demographic index (SDI) levels was also analyzed. Results From 1990 to 2019, the number of deaths and DALYs of diarrhoeal diseases resulting from unsafe water decreased by 50% and 59%, respectively. Moreover, the ASR of deaths and DALYs also decreased during study period, with AAPCs of -3.69 (95% CI [95% confidence interval]: -3.91 to -3.47) and -3.66 (95% CI: -3.8 to -3.52), respectively. High diarrhoeal diseases resulting from unsafe water occurred mainly in low SDI regions and Africa. Males exhibited a greater diarrhoeal deaths attributable to unsafe water than females, which was contrary to the condition in term of DALYs. Age-specific burden of diarrhoeal deaths attributable to unsafe water concentrated in children younger than 5 years. The AAPCs of ASR of both deaths and DALYs showed a strong negative correlation with the SDI levels. Conclusions Current study indicated that the global burden of unsafe water exposure related diarrhoeal diseases decreased from 1990 to 2019 and varied significantly according to age, sex, and geographical location. Effective health promotion and health communication, strategies and policies should be adopted to prevent and control diarrhoeal diseases resulting from unsafe water exposure.